2006
DOI: 10.1176/ajp.2006.163.6.1061
|View full text |Cite
|
Sign up to set email alerts
|

Binge Drinking During Pregnancy as a Predictor of Psychiatric Disorders on the Structured Clinical Interview for DSM-IV in Young Adult Offspring

Abstract: Prenatal exposure to alcohol may be a risk factor for specific psychiatric disorders and traits in early adulthood, even in a nonclinical group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(49 citation statements)
references
References 25 publications
2
43
1
2
Order By: Relevance
“…Replications of these findings in human studies would provide support for a biological origin of some cases of early drinking through a 'programming' effect on the brain's natural reward circuitry and confirm emerging evidence pointing to in utero alcohol exposure in the development of addictions ([Alati et al, 2006], [Baer et al, 2003] and [Barr et al, 2006]). On the other hand, the possibility remains that the effect found is not explained by intrauterine mechanisms, but maybe due to shared familial, environmental and modelling factors, which existing studies have not been able to appropriately taken into account.…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…Replications of these findings in human studies would provide support for a biological origin of some cases of early drinking through a 'programming' effect on the brain's natural reward circuitry and confirm emerging evidence pointing to in utero alcohol exposure in the development of addictions ([Alati et al, 2006], [Baer et al, 2003] and [Barr et al, 2006]). On the other hand, the possibility remains that the effect found is not explained by intrauterine mechanisms, but maybe due to shared familial, environmental and modelling factors, which existing studies have not been able to appropriately taken into account.…”
Section: Introductionsupporting
confidence: 60%
“…The evidence regarding a relationship between in utero alcohol exposure and early alcohol uptake in offspring is limited. Of the studies published to date, three have found an effect in early adulthood ([Alati et al, 2006], [Baer et al, 2003] and [Barr et al, 2006]). In this sample, the effect of in utero exposure to alcohol was not confined to the antenatal period, but appears to persist in childhood.…”
mentioning
confidence: 99%
“…Pesquisas prévias demonstraram a associação entre fumo materno ou alcoolismo durante a gravidez e problemas do comportamento na infância e adolescência 46,47,48 . No nosso trabalho, após ajuste para fumo materno e consumo de álcool na gravidez, as associações entre déficit de peso e IMC para idade ao nascimento se mantiveram significativas.…”
Section: Discussionunclassified
“…Alcohol use in the family, paternal use in particular, has been linked to increased risk of child abuse, as well as future alcohol abuse by children themselves [51][52][53]. This can predispose children to behaviors that can perpetuate the occurrence of FASD as they grow into child bearing years [43,[51][52][53][54][55][56][57]. Therefore, a familial approach in the detection of alcohol use is important for advances in FASD research.…”
Section: Alcohol Use In the Family And Fasdmentioning
confidence: 99%